Điều chế vật liệu nano SiO2 cấu trúc xốp từ tro trấu để hấp phụ xanh metylen trong nước - Thanh Lê, Đặng Thị; Hưng, Nguyễn Văn; Bích, Nguyễn Ngọc; Nghị, Nguyễn Hữu; Bằng, Trần Hữu (Vietnam Journal of Chemistry, 2015)
Mesoporous silica nanoparticles was extracted successfully from rice straw ash (RSA) by using sodium hydroxide solution to produce a sodium silicate solution and then precipitated by adding HCl solution until the pH value about 3. The prepared products were characterized by EDX, XRD, SEM, TEM, FT-IR and BET methods. It was found that the optimal synthesis conditions for the preparation of SiO2 nanoparticles in the weight ratio RSA/NaOH = 1/2.4, respectively and products were calcined at 550oC in 2h. In this condition the obtained SiO2 powders were monoclinic crystal system, mesoporous structure and large specific surface area (258.3 m2/g). Moreover, the performance of nanosized SiO2 powders was tested by the adsorption of methylene blue in a batch system under different adsorbent dosage, different initial dye concentrations and different pH values. The results show that the maximum adsorption capacity was 20.41 mg.g-1 and a high pH is favorable for adsorption. Further, equilibrium isotherms of the adsorption of methylene blue on SiO2 fit well to both the Langmuir model and Freundlich model.